Pengaruh Video dan Leaflet tentang Menstruasi terhadap Kesiapan dalam Menghadapi Menarche: The Effect of education Videos and Leaflets about Menstruation on the Readiness Facing Menarche - Purbowati, Niken; Follona, Willa; Wijayanti, Mustika Eka (Poltekkes Kemenkes Palu, 2021)
Introduction: Readiness to face menarche is needed by teenage girl. Lack of knowledge about menarche can lead to a misconception about menstruation. Objective: The aim of this study was to determine the effect of videos and leaflets on menstruation on the readiness of teenage girl to face menarche. Methods: We used a quasi-experimental pre-posttest study with a control group design. The population of this study were students of class IV and V, the sample was obtained by purposive sampling with a total of 60 divided into two groups, namely the treatment group (n=30) and the control group (n=30). The treatment group was given educational videos and leaflets. Data were analyzed using the Mann Whitney test. Results: There was an increase in the readiness score (mean±SD [34.09 ± 3.49]) and the knowledge score (14.3±1.48) in facing menarche was higher in the treatment group than the readiness score (32.83±4.29) and knowledge scores (9.83±0.76) in the control group. The different test results showed that there are difference in readiness score (p=0.012) and knowledge score (p=0.001) between the treatment and control groups. Conclusion: Interventions in the form of educational videos and leaflets can increase readiness and knowledge to face menarche in teenage girl.